Assessing the effectiveness of performance indicators in health organisations and professionals - Ferreira, A.; Dias, Á. (International Journal of Healthcare Technology and Management, 2023)
Several questions have been raised regarding the credibility, and consequent real value, of the assessment of professional performance as a management tool, considering that there are reports of situations in which the professionals are being evaluated based on objectives to be accomplished rather on the excellence of the performance of its task. As such, this study aims to analyse the introduction of metrics for evaluating the performance of health professionals’ performance indicators, and to identify the changes resulting from the introduction of performance indicators in the evaluation of physicians. Results reveal that physicians feel conditioned in the exercise of their professional activity by the need to comply with established performance indicators. Furthermore, it was also found that the cost reduction in primary health care may be insignificant when compared to the increase in secondary health care costs.